MULTI-FACTORIAL MATHEMATICAL STATISTICAL SIMULATION OF OIL PRODUCTION - Gunay Vagifgiz (World Science, 2021)
Oil and gas deposits differ depending on the bed size, geological-physical development conditions, oil quality and geographic location. Including them in the development is connected with various investments to the main constructions; subsistence and current material expenses also differ. Therefore, from the point of view of economic efficiency, oil and gas deposits are not equal. Location of oil and industry leads to the problem of the sequence of putting of various deposits into operation and their development rate. The sizes of oil and gas beds and available oil and gas reserves in them give reason to say which of these beds will be put into operation in the near future. Completion and development of large scale deposits require less investments compared to small scale deposits. Such deposits are usually highly productive, expenses per a production unit in them is small. All these determined importance of the use of reserves in large scale deposits in the first turn.